COVID‐19 in posttransplant patients—report of 2 cases. Issue 7 (17th April 2020) - Huang, Jiaofeng; Lin, Heng; Wu, Yinlian; Fang, Yingying; Kumar, Rahul; Chen, Gongping; Lin, Su
Abstract : Coronavirus Disease 2019 (COVID‐19) has become a pandemic since March 2020. We describe here 2 cases of COVID‐19 infection in a posttransplant setting. First one is a 59‐year‐old renal transplant recipient; the second is a 51‐year‐old allogeneic bone marrow transplant recipient. Both patients were on immunosuppressant therapy and had stable graft function before COVID‐19 infection. After the diagnosis of COVID‐19, immunosuppressive agents were discontinued and methylprednisolone with prophylactic antibiotics were initiated, however, the lung injury progressed. The T cells were extremely low in both patients after infection. Both patients died despite the maximal mechanical ventilatory support. Therefore, the prognosis of COVID‐19 pneumonia following transplantation is not optimistic and remains guarded. Lower T cell count may be a surrogate for poor outcome. Abstract : This report presents the clinical features, treatment, and outcome of two posttransplant patients with COVID‐19.